Noncitrated blood transfusions used as adjunctive treatment in a 7‐year‐old Shetland Pony with haemoperitoneum due to a ruptured corpus haemorrhagicum. (May 2014) - Fouché, N.; Cornelisse, K.; Gerber, V.; Gurtner, C.; Krudewig, C.; Koch, C.
Summary Chronic bleeding due to extensive haemorrhage from a ruptured corpus haemorrhagicum developed 2–4 weeks after parturition and was identified as the cause for a haemoperitoneum in a 7‐year‐old Shetland Pony mare, leading to anaemia. Diagnosis was made upon exploratory coeliotomy and a unilateral ovariectomy was performed. Intra‐ and post operatively, the mare received autologous blood transfusions of noncitrated blood. To our knowledge, this is the first report of an autologous blood transfusion accomplished using noncitrated blood collected from the abdominal cavity.